YvcI from Bacillus subtilis has in vitro RNA pyrophosphohydrolase activity - Frindert, Jens; Zhang, Yaqing; Ahmed, Yasar Luqman; Sinning, Irmgard; Jäschke, Andres (The journal of biological chemistry, 2019)
RNA degradation is one of several ways for organisms to regulate gene expression. In bacteria, the removal of two terminal phosphate moieties as orthophosphate (Bacillus subtilis) or pyrophosphate (Escherichia coli) triggers ribonucleolytic decay of primary transcripts by 5′-monophosphate-dependent ribonucleases. In the soil-dwelling firmicute species B. subtilis, the RNA pyrophosphohydrolase BsRppH, a member of the Nudix family, triggers RNA turnover by converting primary transcripts to 5′-monophospate RNA. In addition to BsRppH, a source of redundant activity in B. subtilis has been proposed. Here, using recombinant protein expression and in vitro enzyme assays, we provide evidence for several additional RNA pyrophosphohydrolases, among them MutT, NudF, YmaB, and YvcI in B. subtilis. We found that in vitro, YvcI converts RNA 5′-di- and triphosphates into monophosphates in the presence of manganese at neutral to slightly acidic pH. It preferred G-initiating RNAs and required at least one unpaired nucleotide at the 5′-end of its substrates, with the 5′-terminal nucleotide determining whether primarily ortho- or pyrophosphate is released. Exchanges of catalytically important glutamate residues in the Nudix motif impaired or abolished the enzymatic activity of YvcI. In summary, the results of our extensive in vitro biochemical characterization raise the possibility that YvcI is an additional RNA pyrophosphohydrolase in B. subtilis.
Gesehen am 17.01.2020